The Plastid-Encoded RNA Polymerase-Associated Protein PAP9 Is a Superoxide Dismutase With Unusual Structural Features - Favier, Adrien; Gans, Pierre; Boeri Erba, Elisabetta; Signor, Luca; Muthukumar, Soumiya Sankari; Pfannschmidt, Thomas; Blanvillain, Robert; Cobessi, David (Frontiers in Plant Science, 2021)
In Angiosperms, the plastid-encoded RNA polymerase (PEP) is a multimeric enzyme, essential for the proper expression of the plastid genome during chloroplast biogenesis. It is especially required for the light initiated expression of photosynthesis genes and the subsequent build-up of the photosynthetic apparatus. The PEP complex is composed of a prokaryotic-type core of four plastid-encoded subunits and twelve nuclear-encoded PEP-associated proteins (PAPs). Among them, there are two iron superoxide dismutases, FSD2/PAP9 and FSD3/PAP4. Superoxide dismutases usually are soluble enzymes not bound into larger protein complexes. To investigate this unusual feature, we characterized PAP9 using molecular genetics, fluorescence microscopy, mass spectrometry, X-ray diffraction, and solution-state NMR. Despite the presence of a predicted nuclear localization signal within the sequence of the predicted chloroplast transit peptide, PAP9 was mainly observed within plastids. Mass spectrometry experiments with the recombinant Arabidopsis PAP9 suggested that monomers and dimers of PAP9 could be associated to the PEP complex. In crystals, PAP9 occurred as a dimeric enzyme that displayed a similar fold to that of the FeSODs or MnSODs. A zinc ion, instead of the expected iron, was found to be penta-coordinated with a trigonal-bipyramidal geometry in the catalytic center of the recombinant protein. The metal coordination involves a water molecule and highly conserved residues in FeSODs. Solution-state NMR and DOSY experiments revealed an unfolded C-terminal 34 amino-acid stretch in the stand-alone protein and few internal residues interacting with the rest of the protein. We hypothesize that this C-terminal extension had appeared during evolution as a distinct feature of the FSD2/PAP9 targeting it to the PEP complex. Close vicinity to the transcriptional apparatus may allow for the protection against the strongly oxidizing aerial environment during plant conquering of terrestrial habitats.